Violência contra migrantes venezuelanas na perspectiva dos direitos humanos em Boa Vista-Roraima - Silva, Fernando Silva e (2022)
This Master's Thesis has the scope to deal with violence against Venezuelan migrants from the perspective of Human Rights in Boa Vista-Roraima. Violence against women is a phenomenon that manifests the relationship of inequality between men and women, leading to gender violence existing in society. Therefore, it is important to consider the risk and vulnerability scenarios they face, such as the numerous cases of sexual abuse, sexual harassment, exploitation of their workforce, psychological and physical violence, among other situations that are exposed on a daily basis. Thus, the present dissertation has the general objective of analyzing violence against Venezuelan migrant women from the perspective of Human Rights in the municipality of Boa Vista-Roraima, as well as the specific policies and actions to combat it from the perspective of Human Rights, in the period of 2017 to 2021, last five years. The specific objectives are: to verify the causes of violence against Venezuelan migrant women in Boa Vista/RR; determine the typification of the crime committed against the Venezuelan migrant woman victim of violence in Boa Vista/RR; to know the actions that are taken by the State to combat violence against Venezuelan migrant women in a situation of social vulnerability in Boa Vista/RR, from the perspective of Human Rights. In this sense, the research becomes important insofar as it sought to understand the aspects that are involved in increasing the rates of violence against women, especially the increase in violence against Venezuelan migrant women in Boa Vista. In this context, we analyze the violence against Venezuelan migrant women who are in social vulnerability, from the perspective of Human Rights. This research is justified from the need to approach violence against Venezuelan migrant women, from the perspective of Human Rights. This dissertation is organized into four chapters, and its discursive structure is based on a socio-legal analysis, in order to understand the increase in violence against Venezuelan migrant women in Boa Vista. Chapter 1 makes a theoretical discussion anchored in the categories of analysis, State and Migration, Violence and Gender issues. Chapter 2, on Human Rights and Venezuelan Migration. Chapter 3, violence against women in Brazil. The last chapter deals with violence against Venezuelan migrants from the perspective of Human Rights, in Boa Vista, Roraima and, finally, the Final Considerations. In this context, it became evident, in the period under analysis, in relation to violence against Venezuelan migrants from the perspective of Human Rights in Boa Vista-Roraima: that Venezuelan migrant women are subjected to various forms of domestic and family violence, typified in the Maria Law of Penha nº 11.340/2006; that physical violence is the type of violence that has the highest incidence of occurrence, involving Venezuelan migrants, with emphasis on physical violence involving bodily harm, acts of violence and femicide; It was found that Venezuelan migrant women are subjected to various human rights violations during the period of migration to Boa Vista, such as cases of sexual abuse, sexual harassment, exploitation of their workforce, domestic and family violence. The methodology used in the present research is based on the qualitative perspective and used the deductive approach method. As a methodological procedure, bibliographic reviews, documental research, research on local and national newspapers websites and semi-structured interviews with 5 (five) managers who work in bodies dealing with violence against women in Roraima were used, in order to obtain information about the problem presented. The dissertation also collected documentary records from official institutions that work in the process of combating violence against women in Boa Vista, in the last five years, which helped to understand the increase in violence against Venezuelan migrant women.